Pogled na Zid : 1994-1996 : Umetnici i Kriticari. - Cinema Rex, Beograd (Beograd : Fond for an Open Society - Center for Contemporary Art, 1996)
Andelkovic, Jelica Radovanovic & Dejan; Bajic, Mrdan; Bojovic, Slobodan; Cekic, Jovan;Dragojlovic, Marija; Duric, Uros; Fia, Art Group ; Glid, Daniel; Glid,Gabriel ; Grba, Dejan ; Ignjatovic, Dragan Ve. ; Iljovski, Bora ; Jeremic, Moca ; Joksimovic, Zdravko ; Kocic, Nina ; Krgovic, Dobrivoje Bata ; Krnajski, Dragoslav ; Markovic, Sasa ; Markovic, Srdan Dile ; Markus, Stevan ; Milivojevic, Slobodan Era ; Milunovic, Mihael ; Momirov, Zeljka ; Naskovski, Zoran ; Ostojic, Tanja ; Pavic, Branko ; Petkovic, Mihajlo ; Popovic, Milan ; Prodanovic, Mileta ; Pudding, Bumpkins in ; Rackovic, Nenad ; Rafajlovic, Aleksandar ; Skart ; Srdic, Dragan ; Stevanovic, Vera ; Talent ; Todosijevic, Rasa Dragoljub ; Tomic, Milica ; Vasic, Cedomir ; Vlaovic, Darko
Pogled na Zid : 1994-1996 : Umetnici i Kriticari / A Look at the Wall : 1994-1996 : Artists and Critics, projekt, January 1994 - May 1996 / Cinema Rex, Beograd, 1 - 18 July 1996
boek